Maternal-Infant Correlation of Multidrug-Resistant Staphylococcus aureus Carriage: A Prospective Cohort Study - Lin, Jialing; Yao, Zhenjiang (Frontiers in Pediatrics, 2018)
Objectives: We aim to assess the correlation of multidrug-resistant Staphylococcus aureus (MDR S. aureus) carriage between mothers and their newborn infants. Materials and Methods: We conducted a prospective cohort study of mothers and their newborn infants in two hospitals in Shenzhen, China, from August to November 2015. We collected demographic and clinical information of mothers and newborn infants by face-to-face questionnaire and medical dataset. Serial swabs were collected from mothers and their newborn infants for further experiments. Maternal-infant correlation was assessed using the Poisson regression model. Results: The prevalence of MDR S. aureus vaginal carriage in mothers was 4.7% (86/1834). The incidence of MDR S. aureus carriage in newborn infants were 1.3% (23/1834). The adjusted relative risk and 95% confidence interval of maternal-infant MDR S. aureus carriage was 7.63 (2.99-19.49). Six MDR S. aureus maternal-infant pairs were concordant. The phenotypic and molecular characteristics of MDR S. aureus isolates were similar between mothers and their newborn infants. Conclusion: MDR S. aureus vaginal carriage in mothers was associated with an increased risk for MDR S. aureus carriage in their newborn infants.